Economic Diplomacy of the Bandung City Tourism and Culture Office through the Visit IMT-GT Program 2023-2025 to Enhance Tourist Visits in Bandung - Siti Salwa Sapitri; Firda Istigosari; Lilis Karlina; Rijal Aditia (Trasearch (Training, Research and Academy Society, 2025)
Economic diplomacy is one of the important strategies in increasing tourist visits to the city of Bandung, especially through the 'Visit IMT-GT Year 2023-2025 program. The Bandung City Tourism and Culture Office is committed to utilizing this program as a means to strengthen regional cooperation with IMT-GT (Indonesia-Malaysia-Thailand Growth Triangle) member countries. The policies implemented include international cooperation through sister city schemes, tourism destination promotion, tourism infrastructure development, improving the quality of human resources, and organizing cultural activities and art exchanges. Through these strategic steps, the Tourism and Culture Office aims to attract more tourists, introduce local cultural richness, and increase the competitiveness of Bandung City tourism at the international level. The expected results from the implementation of this program are an increase in the number of tourist visits that have a positive impact on the local economy and strengthening relations between countries in the IMT-GT region.